PUBLIC REACTIONS TO FATWA DECISIONS BASED ON THE KIRKPATRICK ASSESSMENT MODEL - Kamarudin Ahmad; Solahuddin Abdul Hamid; Mohd Akram Dato’ Dahaman@Dahlan; Azman Md Zain; Mohd Nizho Abdul Rahman; Zulhilmi Paidi (Journal of Islamic, Social, Economics and Development, 2017)
Fatwa commence from the society and they are directly involved in accepting andpracticing it. It means, the fatwa is a legal answer in response to the issues arising. Therefore,the community must accept and understand every fatwa. This paper will look at the public'sreaction to a fatwa if it can affect them. Reaction is the first stage in Kirkpatrick's assessmentmodel consisting of four levels. This level will measure the effectiveness of a fatwa issued. Thislevel of assessment is important because the public's reaction to the fatwa program willdetermine the effectiveness of the next level. Even if a fatwa is authoritative or legitimate fromthe aspect of Islamic legal theory and is believed by the public to be legitimized and correct inaccordance with Islamic law, but still there are some dispute over the effectiveness and thedecision of the fatwa issued